Upaya Melestarikan Nilai-Nilai Karakter Remaja Berbasis Kearifan Lokal - Nidra Oganta, Riga; Sukarno, Sukarno; Yunarman, Sepri (Yayasan Darussalam Bengkulu, 2022)
This research is motivated by the problem of preserving the forms of character that arise from local wisdom and efforts to preserve character in the youth of Pasar Sebelat Village, North Bengkulu Regency. This type of research is a field research, namely: a research that is carried out systematically by lifting existing data in the field, where the researcher is the key instrument, the data collection technique is done by triangulation. Data collection techniques using observation, interviews, and documentation. The informants of this study consisted of village officials, traditional leaders and the community. The data analysis technique used qualitative methods, namely using the method of interactive analysis. Efforts to preserve the character values ​​of youth based on local wisdom can help adolescents form better character values ​​through the local wisdom of the Pekal Tribe. creative and religious. Efforts to preserve the values ​​of adolescent character are carried out by the family, village officials, traditional leaders, Gandai and Basilek Imau dance trainers and the community.